Solventless solid‐phase extraction using Zn ion‐imprinted polymer detected by colorimetric method. (3rd January 2022) - Lee, Yelin; Ahn, Soyoung; Cho, Hansang; Ogunro, Vincent; Bae, Sunyoung
Abstract: Ion‐imprinted polymers attract a lot of attention and are actively studied because of easy preparation and their high selectivity. Zn is known to be essential mineral in human body; however, when it is absorbed into our body, it is hardly discharged completely and causes various disease or side effects. To suggest new method for selective Zn extraction, Zn ion‐imprinted polymer (ZIIP) was synthesized by bulk polymerization and NZIIP (non‐ZIIP) was prepared as a control. Then, ZIIP and NZIIP were characterized by Fourier‐transform infrared spectroscopy, Scanning electron microscope, and X‐ray photoelectron spectroscopy to investigate structural changes during polymerization. Adsorption isotherm studies indicated that sigmoidal Langmuir isotherm equation was fitted well and the maximum adsorption capacity and affinity of Zn on ZIIP was superior to NZIIP. Dithizone was used to chelate with Zn in supernatant for colorimetric determination. ZIIP‐solid‐phase extraction potentially used as Zn ion filter was investigated showing good removal efficiency. Abstract : Zn ion‐imprinted polymer selectively binds Zn ion with dithizone for colorimetric determination.